Effectiveness of a School Intervention Based on Knowledge, Attitude, and Practice of Soil-Transmitted Helminths - de Freitas, Viviany Viriato [UNESP]; Madeira, Newton Goulart [UNESP] (American Society of Tropical Medicine and Hygiene, 2024)
More than 1.5 billion people are infected by soil-transmitted helminths (STHs) worldwide, comprising one of the world’s most serious public health problems. School-age children are the most affected as a result of precarious hygienic habits, especially in economically poor areas that lack appropriate sanitation. Therefore, this study aimed to evaluate a didactic method via a health education approach as a complement to the school curriculum of the sixth-grade students of public schools, distributed among six cities in the state of São Paulo, Brazil. For this, a didactic booklet was elaborated with educational explanatory activities about worms, their life cycle, and how to avoid infections. The intervention was measured by the change caused by knowledge, attitude, and practice (KAP), in students before and after using the notebook, through a questionnaire with high validity and internal consistency. Schools were assigned randomly into intervention and control groups, receiving both the didactic material and the questionnaires, versus the questionnaires only, respectively. The results were submitted to an analysis of covariance that revealed a significant difference pre- and postintervention for knowledge (P, 0.001), with greater means (0.54) compared with the control group (0.44); attitude (P, 0.005), with respective means of 0.56 versus 0.48; and practice (P, 0.001), with means of 0.75 versus 0.57. These findings set the didactic material as a potential tool to complement the school curriculum through KAP without disrupting the teaching system, in addition to assisting teachers in health education at schools aiming to prevent children’s infections by STHs.